2021
DOI: 10.1515/biol-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circRNA circ-CSPP1 as a potent driver of colorectal cancer by directly targeting the miR-431/LASP1 axis

Abstract: Colorectal cancer (CRC) is the third most common malignancy worldwide. Circular RNAs (circRNAs) have been implicated in cancer biology. The purpose of the current work is to investigate the precise parts of circRNA centrosome and spindle pole-associated protein 1 (circ-CSPP1) in the progression of CRC. Our data showed that circ-CSPP1 was significantly overexpressed in CRC tissues and cells. The knockdown of circ-CSPP1 attenuated cell proliferation, migration, invasion and promoted apoptosis in vitro and weaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In this study, the authors determined a gene signature for FOLFOX based on the gene expression of 14 classifier genes. In more detail, the 14-gene signature was constituted by different genes, including the smad ubiquitin regulatory factor 2 ( SMURF2 ), a negative regulator of TGF-β signaling with a tumor-suppressive role [ 107 ], the Mbt domain containing 1 ( MBTD1 ), encoding a potent transcriptional coactivator [ 108 ], the adaptor related protein complex 3 subunit Mu 2 ( AP3M2 ), the RING finger protein 141 ( RNF141 ), a gene reported to interact with KRAS promoting CRC progression [ 109 ], the aminopeptidase puromycin sensitive ( NPEPPS ), encoding key zinc metallopeptidases [ 110 ], the bromodomain PHD finger transcription factor ( BPTF ), a chromatin remodeling-related gene [ 111 ], the family with sequence similarity 73, member A ( FAM73A ), the amyloid beta precursor protein binding protein 2 ( APPBP2 ), the archaelysin family metallopeptidase 2 pseudogene 1 ( AMZ2P1 ), the SLIT-ROBO rho GTPase activating protein 1 ( SRGAP1 ), that encodes a protein mediating cell migration associated with CRC tumor progression and poor prognosis [ 112 ], the N-myristoyltransferase-1 ( NMT1 ), necessary for lysosomal degradation and mammalian target of rapamycin (mTOR) signaling pathway [ 113 ], the centrosome and spindle pole associated protein 1 ( CSPP1 ), whose circ-CSPP1 was found to be significantly overexpressed in CRC tissues [ 114 ], the eukaryotic translation initiation factor 1 ( EIF1 ), and the centrosomal protein 290 ( CEP290 ) genes. Using the 14- gene classifier, the learning model was capable of classifying responders with an overall SE of 91.3% compared with non-responders with 95.6% in SP, achieving an ACC of 80.2%.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the authors determined a gene signature for FOLFOX based on the gene expression of 14 classifier genes. In more detail, the 14-gene signature was constituted by different genes, including the smad ubiquitin regulatory factor 2 ( SMURF2 ), a negative regulator of TGF-β signaling with a tumor-suppressive role [ 107 ], the Mbt domain containing 1 ( MBTD1 ), encoding a potent transcriptional coactivator [ 108 ], the adaptor related protein complex 3 subunit Mu 2 ( AP3M2 ), the RING finger protein 141 ( RNF141 ), a gene reported to interact with KRAS promoting CRC progression [ 109 ], the aminopeptidase puromycin sensitive ( NPEPPS ), encoding key zinc metallopeptidases [ 110 ], the bromodomain PHD finger transcription factor ( BPTF ), a chromatin remodeling-related gene [ 111 ], the family with sequence similarity 73, member A ( FAM73A ), the amyloid beta precursor protein binding protein 2 ( APPBP2 ), the archaelysin family metallopeptidase 2 pseudogene 1 ( AMZ2P1 ), the SLIT-ROBO rho GTPase activating protein 1 ( SRGAP1 ), that encodes a protein mediating cell migration associated with CRC tumor progression and poor prognosis [ 112 ], the N-myristoyltransferase-1 ( NMT1 ), necessary for lysosomal degradation and mammalian target of rapamycin (mTOR) signaling pathway [ 113 ], the centrosome and spindle pole associated protein 1 ( CSPP1 ), whose circ-CSPP1 was found to be significantly overexpressed in CRC tissues [ 114 ], the eukaryotic translation initiation factor 1 ( EIF1 ), and the centrosomal protein 290 ( CEP290 ) genes. Using the 14- gene classifier, the learning model was capable of classifying responders with an overall SE of 91.3% compared with non-responders with 95.6% in SP, achieving an ACC of 80.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Xi et al found that circCSPP1 knockdown inhibited the growth of Doxorubicin-resistant CRC cells and enhanced doxorubicin sensitivity through the miR-944/FZD7 axis, providing a potential target for CRC therapy ( Xi et al, 2021 ). In addition, it was also found that knockdown of circCSPP1 promoted apoptosis and weaken tumour growth in vivo , providing evidence for circCSPP1 as a promising biomarker for CRC management ( Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some circRNAs are up-expressed in CRC tissues and cells, and play an oncogenic role by regulating downstream target genes or activating certain signaling pathways. In 154 oncogenes, 23 circRNAs were repeatedly studied, among which the most frequently studied were circ_0007142 ( Zhu et al, 2019 ; Yin et al, 2020 ; Wen et al, 2021 ) and circCSPP1 ( Wang et al, 2020a ; Li et al, 2021 ; Xi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations